Decision Making of Indonesian Migrant Workers in Donomulyo District, Malang Regency - Nurwidayanto, Moch. Alfin; Budijanto, Budijanto; Deffinika, Ifan; Oraby, Ghada Abd Elsattar Mohammed (Humanities Horizon, 2024)
This study aims to analyze the socioeconomic and demographic conditions of Indonesian migrant workers in Donomulyo District and identify the factors influencing their decision to migrate. Using a quantitative descriptive approach, the research was conducted in Donomulyo District, Malang Regency, with a population of 722 individuals whose family members work as migrant workers. A sample of 88 respondents was determined using the Slovin formula and proportional random sampling. Data were collected through field observations and interviews, processed using single and cross-tabulations, and analyzed with inferential statistics, specifically the Chi-Square test. The results show that migrant workers in Donomulyo District predominantly have a junior high school education, are married, and support an average of three dependents. Before migration, most were engaged in agriculture, either as laborers or self-employed, earning between IDR 1,500,000 and IDR 2,000,000, with an average land ownership of 0.09-0.2 hectares. Among the variables studied, the most significant factor influencing migration decisions was their previous occupation in agriculture. These findings highlight the socioeconomic challenges faced by rural communities and their influence on migration patterns, providing insights for policymakers in addressing migration-related issues.